Unsettling the Settler: Disillusionment and Narrative Fragmentation in Karen Blixen’s Out of Africa - Sameera Abbas (University of Chitral Journal of Linguistics and Literature, 2023)
This paper examines Karen Blixen’s Out of Africa through a close reading of Chapter Four, “From an Immigrant’s Notebook,” to explore how the memoir drifts from a romanticized colonial imagery toward a more fragmented and ambivalent portrayal of empire. While much of the text is steeped in aesthetic nostalgia, this chapter signals a shift—both in form and in tone—toward disillusionment. Blixen’s use of digressive reflections in this chapter destabilizes the coherence of the colonial narrative she had previously upheld, drawing attention to the tensions between belonging and estrangement, memory and forgetting, permanence and displacement. By foregrounding these thematic contradictions, the paper argues that Blixen inadvertently unsettles the very imperial ideologies her text seems to admire.